Social media adoption in smes sustainability: evidence from an emerging economy - John Amoah; Emmanuel Bruce; Zhao Shurong; Sulemana Bankuoru Egala; Kofi Kwarteng (Cogent Business & Management, 2023)
Social media is constantly changing the business landscape across all economic sectors. Given this, small and medium enterprises (SMEs) are leveraging this to give their businesses a new trend. In emerging economies, however, the rate of adoption and integration of social media among small and medium enterprises appears to have lagged due to a multitude of factors. Drawing on the technology organization and environment (TOE) framework, the purpose of this study was to investigate the factors affecting social media application adoption and their impact on SMEs' sustainability in Ghana's context. Data was collected from 430 managers of SMEs in Ghana using a structured questionnaire and analyzed using a PLS-SEM. Findings revealed that cost-effectiveness, customer pressure, employees' competence, financial resource availability, and leaders' support positively influence social media adoption, while social media adoption also impacts SME firms' sustainability. A negative effect was, however, observed for factors like industry pressure, perceived complexity, relative advantage, and perceived compatibility. This study contributes to the rising deployment of social media by businesses to improve their competitiveness. The implications of the research are also discussed.
Keywords: 650; SME; Social media; Sustainability; Technology adoption; TOE